HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU HAMILTENTANG ANTENATAL CARE TERHADAP KEPATUHAN KUNJUNGAN KEHAMILAN DI PMB RABIAH PALEMBANG TAHUN 2020 - Nelly Mariyam; Latifah; Meta Rosdiana; Tiara Pratiwi; Mardelia Astriani (LPPM STIKes Mitra Adiguna, 2022)
Abstrak Antenatal care (ANC) is a planned program in the form of observation, education, and medical treatment in pregnant women to obtain a process of pregnancy and childbirth are safe and satisfactory. On 2019, the coverange pregnant women visits (K1) at 96,73% and pregnant women visits (K4) at 95,19%.The purpose from this research is to know the Relationship characteristic and knowledge of pregnant women about Anc toward pregnancy visits. Kinds of this research used analytic survey through Cross Sectional approch. The population from this research were all the pregnant women in Alia Medika Health Center Palembang with the sample 61 respondents which took with accidental sampling technic. Data processed in a univariat analysis and bivariat analysis with Chi-Square test. The results from this research showed pregnant women with age at risk there were 70,5% and pregnant women not risk 29,5% and pregnant women with good knowledge there were 85,2% and low education 14,8%, pregnant women with good knowledge there were 85,2% and low knowledge 14,8% and pregnant women who work 73,8% and who did not work 26,2%. This research used Chi-Square test showed there was correlation between mother’s age with compliance visit pregnancy pregnant women’s knowledge about ANC toward pregnancy visits with p value = 0,029 and there was correlation between mother’s education with compliance visit pregnancy pregnant women’s knowledge about ANC toward pregnancy visits p value = 0,016 there was correlation between mother’s knowledge with compliance visit pregnancy pregnant women’s about ANC toward pregnancy visits with p value 0,016 there was correlation between mother’s job with compliance visit pregnancy pregnant women’s about ANC toward pregnancy visits with p value 0,048. Hoped for Alica Medica Health Center Palembang to improve service (K1-K4) appropriate national standards targets for society especially pregnant women.